COMMUNICATION STRATEGY OF FIELD AGRICULTURAL EXTENDERS IN THE SOCIALIZATION OF RICE AGRICULTURAL INNOVATIONS IN DRY LAND TO FARMERS GROUP IN JATIGREGES VILLAGE, PACE DISTRICT, NGANJUK REGENCY - Rofi Wahyu Aditama; Heidy Arviani; Zainal Abidin Achmad; Ririn Puspita Tutiasri (JOSAR (Journal of Students Academic Research), 2021)
Communication and development are two things that cannot be opened and are closelyrelated. One sector that requires a special touch of development communication is the agriculturalsector. This study was to determine the communication strategy of Field Agricultural Extension indisseminating innovations in dryland rice cultivation to farmer groups in Jatigreges Village, PaceDistrict, Nganjuk Regency. The research method used is descriptive qualitative. The data in thisstudy were collected by interview, observation and documentation. Then it is processed usingHafied Cangara's Five-Step communication strategy theory and the Innovation Diffusion Theorycreated by Everett M. Rogers. The results showed that the Field Agricultural Extension did thecommunication stages, namely research, planning, implementation, measurement, and reporting.The communication strategy implemented by PPL was relatively successful because 89.7% of thetargets for the implementation of the innovation program for rice cultivation were in dry land. This isbecause an innovation program contains important points from the theory of diffusion of innovation,namely, compatibility, complexity, testability, and observability.